"He Needed Just About Everything": Caring for Aging Adults Postincarceration. (December 2021) - Jimenez, Laylla B.; Cross, Sarah H.; Boucher, Nathan A.
Little is known about the experiences of caregivers for older adults reentering communities following incarceration. We sought to explore the challenges faced by such caregivers in Central North Carolina. Methods: We conducted a thematic analysis on semi-structured interviews with 11 caregivers. Results: Caregivers discussed how prior incarceration coupled with aging present barriers to housing, employment, and safety-net benefits—making caregiving more difficult. Caregivers assist their older care recipients to develop essential life skills (e.g., scheduling tasks, applying for services) and navigate the dynamic aging process (e.g., loneliness, illness). Caregivers struggle to gain care recipients' trust, often due to their past trauma. Discussion: Caregivers play essential roles supporting older adults postincarceration, yet they experience significant challenges with limited resources. This study informed the development of a resource guide to assist caregivers. Dedicated programs and policies are needed to address these needs at the local level.